2022
DOI: 10.3389/fimmu.2022.861262
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Binding and Nuclear Retention Features of Zebrafish IRF Family Members in IFN Response

Abstract: Interferon regulatory factors (IRFs) constitute a family of transcription factors that synchronize interferon (IFN) antiviral response through translocating to nucleus and binding to the promoters of IFN and IFN-stimulated genes (ISGs). Fish contain 11 IRF members; however, whether or how fish IRF family genes function in IFN response remains limited. Herein, we determine the regulatory roles of 11 zebrafish IRF family members in IFN response relevant to their subcellular localization and promoter binding. Zeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…To strengthen the findings above, nuclear-cytoplasmic separation experiments were performed to detect nuclear translocation of IRF3, a landmark event of RLR-triggered IFN response ( 23 , 42 ). Successful nuclear-cytoplasmic separation was verified by detection of Lamin A/C only in nucleus, and α-tubulin mostly in cytoplasm ( Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To strengthen the findings above, nuclear-cytoplasmic separation experiments were performed to detect nuclear translocation of IRF3, a landmark event of RLR-triggered IFN response ( 23 , 42 ). Successful nuclear-cytoplasmic separation was verified by detection of Lamin A/C only in nucleus, and α-tubulin mostly in cytoplasm ( Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…Successful nuclear-cytoplasmic separation was verified by detection of Lamin A/C only in nucleus, and α-tubulin mostly in cytoplasm ( Figure 2E ). Fish IRF3 is a typical IFN-inducible protein ( 23 , 42 ). Consistently, overexpression of DrLGP2 alone in EPC cells increased the protein level of IRF3 in cytoplasm (lanes 2 and 3 versus lane 1 in Figure 2E ) and also in nucleus (lanes 5 and 6 versus lane 4 in Figure 2E ), indicating that DrLGP2 alone indeed activates IFN response in fish cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the up-regulation of five IRFs (IRF1/3/7/9/10) was observed in SCRV-infected SCSC cells. It has been reported that fish contain 11 IRFs [30]. IRF3 and IRF7 are the two main regulators of IFN expression, which are triggered by PRRs [31].…”
Section: Discussionmentioning
confidence: 99%